Myocardial infarction and thrombolysis. Electrocardiographic short term and long term results using precordial mapping. Issue 1 (July 1985) - von Essen, R; Schmidt, W; Uebis, R; Edelmann, B; Effert, S; Silny, J; Rau, G
Abstract : In a consecutive series of 56 patients with acute myocardial infarction, ST segment depression and elevation in the electrocardiographic limb leads I, II, and III were summated for each patient before and immediately after intracoronary streptokinase infusion and the results compared with the angiographic findings. Forty three patients had angiographically confirmed reperfusion of an initially occluded vessel and showed a significant decrease in summated ST shift. The ST segment changes in the limb leads virtually returned to normal in all 43 patients, and in most, inverted T waves developed. Thrombolysis was unsuccessful in 10 patients, and the infarct related coronary artery was already patent in three. When these two groups are combined, all 13 patients without reperfusion showed no significant change in summated ST segment shift. During percutaneous transluminal angioplasty inflation of the balloon in the vessel that was previously occluded simulated reocclusion and was followed by new ST elevation if the artery supplied viable myocardium. In a further consecutive study of 54 patients with anterior myocardial infarction, the precordial R waves and Q waves were studied over the four to six months following infarction using a standardised 48 electrode mapping system. All patients underwent a repeat angiogram after four to six months. In 36 patients the infarct related vessel was patent. They showed a significant mean increase in summated precordial R wave amplitude and a reduction in the mean number of precordial leads without R waves. In 18 patients with unsuccessful thrombolysis or reocclusion there was a further reduction in mean summated R wave amplitude and an increased number of precordial leads not showing R waves. Precordial R wave mapping seems to be a valuable non-invasive method of assessing the salvage of myocardium after reperfusion and the damage caused by reocclusion. Loss of R waves in the acute phase of myocardial infarction does not necessarily mean an irreversibly damaged myocardium.